Qualitative video analysis as a pedagogical tool in artistic gymnastics - Coelho Bortoleto, M. A.; Duarte Peixoto, C. J. (High performance gymnastics, 2014)
A qualitative analysis of videos is an important tool that can be used throughout the processes of teaching and learning, as well as in the training of motor skills in artistic gymnastics (AG). The use of this tool has grown significantly during the last two decades due to the development of specific computer systems (software / computer programs). This kind of analysis represents a simplified system for observation, registering, and analysis of motor skills and techniques obtained from images of daily training or competition (Hauw & Durand, 2007). The parameters that make up the qualitative descriptive analysis of body movements differ in relation to the objectives of motor skills being analyzed, as well as in relation to the characteristics of the sport, with the goal of obtaining data which will enable the immediate adjustment of distinct technical aspects. Therefore, this resource presents itself as an important tool for coaches of different sports modalities where the technical execution represents a fundamental aspect of the performance.